Killing commendatore - Murakami, Haruki (Vintage, 2018)
When a thirty-something portrait painter is abandoned by his wife, he holes up in the mountain home of a famous artist. The days drift by, spent painting, listening to music and drinking whiskey in the evenings. But then he discovers a strange painting in the attic and unintentionally begins a strange journey of self-discovery that involves a mysterious ringing bell, a precocious thirteen-year-old girl, a Nazi assassination attempt and a haunted underworld.